2019
DOI: 10.1002/cne.24783
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protocadherin‐γC4 protein in the rat brain

Abstract: It has been proposed that the combinatorial expression of γ‐protocadherins (Pcdh‐γs) and other clustered protocadherins (Pcdhs) provides a code of molecular identity and individuality to neurons, which plays a major role in the establishment of specific synaptic connectivity and formation of neuronal circuits. Particular attention has been directed to the Pcdh‐γ family, for which experimental evidence derived from Pcdh‐γ‐deficient mice shows that they are involved in dendrite self‐avoidance, synapse developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
(213 reference statements)
0
5
0
Order By: Relevance
“…γ-Pcdhs also have three C-like variable exons that are expressed in neurons (Kaneko et al, 2006;Phillips et al, 2017). Mice lacking one of the γ-Pcdh-C3, C4 or C5 isoforms died due to neuronal apoptosis, similar to mice lacking all γ-Pcdhs, suggesting that these C-type-isoforms play a special role in the neuronal survival (Chen et al, 2012;Peek et al, 2017;Miralles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…γ-Pcdhs also have three C-like variable exons that are expressed in neurons (Kaneko et al, 2006;Phillips et al, 2017). Mice lacking one of the γ-Pcdh-C3, C4 or C5 isoforms died due to neuronal apoptosis, similar to mice lacking all γ-Pcdhs, suggesting that these C-type-isoforms play a special role in the neuronal survival (Chen et al, 2012;Peek et al, 2017;Miralles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Brains were cryoprotected with 30% sucrose, frozen, and sectioned with a freezing microtome (25 μm thick) and stored in 0.02% sodium azide in 0.1 M PB, pH 7.4 at 4 °C. Immunofluorescence was performed as described elsewhere (Li et al, 2005a;Fekete et al, 2017;Miralles et al, 2020). Briefly, free-floating brain sections were incubated with 5% normal goat serum, 0.3% Triton X-100 in 0.1 M PB for 1 hour at room temperature.…”
Section: Tissue Preparation Immunohistology and Image Acquisitionmentioning
confidence: 99%
“…Clustered Pcdhs are widely expressed in the developing and adult central nervous systems [11,34,35,42,53,[87][88][89][90]. The expression of members of the Pcdha cluster is highly specific to the central nervous system.…”
Section: Cell-specific and Stochastic Expression Of Clustered Pcdh Genesmentioning
confidence: 99%
“…While members of the Pcdh β and γ clusters are prominently expressed in the central nervous system, they are also expressed in several other tissues such as the kidney and lung [ 87 , 89 , 91 ]. Detailed expression patterns of each isoform were initially analyzed by in situ hybridization using isoform-specific probes, which showed that they are stochastically expressed in neuronal subpopulations in various brain nuclei or regions [ 35 , 42 , 53 , 89 , 90 , 92 ].…”
Section: Mechanisms For Generating Clustered Pcdh Codes Of Neuronal Imentioning
confidence: 99%